1982
DOI: 10.1071/bi9820565
|View full text |Cite
|
Sign up to set email alerts
|

Oxine, Ferric Oxine and Copper Oxine as Inhibitors of Growth and Differentiation of Allomyces macrogynus

Abstract: Oxine is an inhibitor of growth and differentiation in A. macrogynus. Growth was inhibited by as little as 4 Jlg/ml and the first effect observed was inhibition of nucleic acid synthesis, followed by inhibition of protein synthesis. Consistent inhibition by oxine of the development of zoosporangia in starving plants required a concentration of 60 Jlg/m!. The degradation of RNA, always observed in starving plants, continued in the presence of oxine, showing that this is an independent phenomenon. When glucose w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…It was originally suggested that trehalose might have a regulatory function because it was synthesized but not utilized by A. macrogynus. Increased synthesis of trehalose in the presence of oxine and of cycloheximide suggested that trehalose production was controlled by an unstable protein or the product of an unstable enzyme (Youatt 1982b). Results with trehalose synthesis by Dictyostelium discoideum suggest the possibility of a similar control process in that organism.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It was originally suggested that trehalose might have a regulatory function because it was synthesized but not utilized by A. macrogynus. Increased synthesis of trehalose in the presence of oxine and of cycloheximide suggested that trehalose production was controlled by an unstable protein or the product of an unstable enzyme (Youatt 1982b). Results with trehalose synthesis by Dictyostelium discoideum suggest the possibility of a similar control process in that organism.…”
Section: Discussionmentioning
confidence: 98%
“…RNA degradation occurred whenever plants were transferred to starvation or semi-starvation conditions. RNA was still degraded when differentiation was inhibited by oxine (Youatt, 1982b). When glucose was added to plants which had been suspended in glutamate solution for 6•5 h, the development of resistant sporangia still occurred even though the RNA content had already reached its minimum concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The total development of the zoosporangium is completed in 3 h and the involvement of stable mRNA for the whole process was easily demonstrated in the presence of actinomycin or oxine (Youatt 1982c). The maturation of resistant sporangia to the stage of spore release has not been described in less than 2 days (Machlis and Ossia 1953;Youatt 1973Youatt , 1980a.…”
Section: Discussionmentioning
confidence: 99%
“…The prevention of this transcription by the supply of single amino acids requires rapid accumulation of the amino acid and is probably best explained by the enzymic production of ammonia at an appropriate site (Sandars and Youatt 1983). If glucose is available the trehalose-synthesizing enzymes are activated by amino acid deficiency and the trehalose content begins to rise even in the presence of cycloheximide (Youatt 1982b). One way of envisaging this activation is by protease action since amino acid deficiency does not prevent the maintenance of amino acid pools and protein turnover was demonstrated by Burke et al (1972) in similar conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Trehalose accumulated to a higher concentration than in controls with glucose only-in one experiment to 98 J.Lg trehalose per milligram dry weight compared with 50 J.Lm/mg in the control. This was reminiscent of the effect of cycloheximide which also altered the maximum content of trehalose reached (Youatt 1982b).…”
Section: Externally Supplied O-ethylhomoserinementioning
confidence: 99%